2002
DOI: 10.2117/psysoc.2002.222
|View full text |Cite
|
Sign up to set email alerts
|

Metacognitive Experiences, Self-Concept, and Self-Regulation

Abstract: The study aimed at identifying the role of metacognitive experiences (ME), such as feeling of difficulty, estimate of solution correctness and estimate of effort exerted, in the formation of one's self-concept in the mathematics domain and in selfregulation. The idea was that when one enters an achievement situation, one's selfconcept in the respective domain will influence the ME evoked in response to the task at hand. The ME, in their turn, will influence and shape one's task-specific selfconcept and through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 40 publications
(34 reference statements)
3
34
0
5
Order By: Relevance
“…Essentially, it is an evaluation of one's capacity. Efklides and Petkaki (2005) found that selfconcept affects mood as well as ME, such as feeling of difficulty and estimate of effort (see also Efklides & Tsiora, 2002). (3c) Motivation.…”
Section: Factors Affecting Effort Allocation Policymentioning
confidence: 96%
See 1 more Smart Citation
“…Essentially, it is an evaluation of one's capacity. Efklides and Petkaki (2005) found that selfconcept affects mood as well as ME, such as feeling of difficulty and estimate of effort (see also Efklides & Tsiora, 2002). (3c) Motivation.…”
Section: Factors Affecting Effort Allocation Policymentioning
confidence: 96%
“…This is due to the fact that both monitoring and control have various facets that interact with each other and with other factors. Such factors are previous knowledge and skills, personality factors, as well as situational factors affecting performance (Efklides et al, 1997(Efklides et al, , 1998(Efklides et al, , 1999Efklides & Tsiora, 2002).…”
mentioning
confidence: 99%
“…In adults, academic self-concepts (see Efklides and Tsiora 2002 ;Kröner and Biermann 2007 ) and metacognitive self-beliefs regarding competencies of one's own reasoning abilities positively predicted con fi dence levels after controlling for accuracy of performance (Kleitman 2008 ;Kleitman and Stankov 2007 ;Stankov and Lee 2008 ) . Our fi ndings indicate similar results with children.…”
Section: The Most Important Internal Factors: Self-beliefsmentioning
confidence: 99%
“…This is so, because they feed on one's self-concept and motivation and, thus, influence future decisions regarding the engagement, or not, in similar tasks (Efklides & Tsiora, 2002). Therefore, metacognitive experiences are critical for selfregulated learning.…”
Section: Metacognitive Experiences and Micro-level Analysismentioning
confidence: 99%